CYBERMACS ERASMUS MUNDUS PROJECT AS AN INNOVATIVE, INDUSTRY-FOCUSED INTERNATIONAL COLLABORATION ON CYBERSECURITY EDUCATION - Gücüyener, A; Dilan, E; Dimitrova, Vesna; CHorbev, Ivan; Creutzburg, R; Dag, H (IATED, 2024)
The dramatic rise in cyber-attacks has made cybersecurity a significant global concern. The cost of cybercrime to the world economy was about $1 trillion in 2020. Along with the increased demand for cybersecurity experts, the changing landscape of cybersecurity threats requires the urgent need for comprehensive, dynamic, and applied cybersecurity education to qualify cybersecurity professionals to prevent, mitigate, and manage cyber threats. In this paper, we propose an innovative teaching and learning approach that brings together academia and industry to address the growing talent gap in cybersecurity, called CyberMACS. CyberMACS, funded by Erasmus+ Mundus Framework, is a Joint Master's Degree Programme in "Applied Cybersecurity", offering a full-time 2-year European MSc programme to provide a solid cybersecurity background on educating future cybersecurity experts to detect, prevent, mitigate, and manage cyber-attacks. CyberMACS is a robust institutional and international collaboration operation for demonstrating European excellence in higher education with a high-level integrated and transnational study programme on applied cybersecurity targeting the best students worldwide. The innovative teaching and learning methodology of CyberMACS relies on four main dimensions: (i) close cooperation with industry, (ii) dynamicity in a curriculum focusing not only on complex technical competencies but also soft skills, (iii) collaborative working culture among three international Higher Education Institutions (HEIs), (iv) international mobility opportunities that are provided to students. In addition to the solid international mobility component, in coherence with the need analysis in the cybersecurity industry, the programme outcomes are designed to prepare students for a multidisciplinary career and for employment opportunities in cybersecurity companies, consulting firms, public/private companies that have cybersecurity/information security departments, including critical infrastructures operators such as power system, transportation systems, and financial technologies. Finally, with respect to the nature of the cybersecurity industry and rising needs, CyberMACS has a solid focus on consolidating the students' soft skills and teaching them how to think outside the box. In that sense, the Curriculum and the teaching methodology of the joint events (i.e. Summer Schools) are established to lead students to put into practice the following specific skills: critically analyse, synthesise, interpret and summarise complex scientific processes; ability to examine the technological, economic, human, legal, organisational, socio-political and policy challenges in the cybersecurity field; design strategies that integrate best practices in cybersecurity, regulatory compliance, and risk management; gain hands-on experience, developing and executing integrated strategies, policies, and safeguards to manage cybersecurity risks across any organisation. In line with this given background, in this paper, we aim to disseminate our innovative teaching methodology, best practices, and limitations for creating an international teaching collaboration on a dynamic and industry-focused discipline such as cybersecurity. While we aim to present CyberMACS' methodology to reach the best students worldwide, we intend to demonstrate how an international talent pipeline can be established and sustained in a field where the demand for skills constantly surges.
Keywords: CyberMACS, cybersecurity, innovation in higher education, international collaboration, university-industry cooperation, human element in cybersecurity, cyber ecosystem.